Insurance for handling employee entitlements in the event of employer insolvency (bankruptcy) - Karaleu, Yury Y. (Ubezpieczenie pracowników przed bankructwem pracodawcy, 2016)
Among the modern types of economic insurances, the insurance of employees to cover their entitlements in the case of insolvency (bankruptcy) of a business may be considered as the most advantageous and future-oriented after the recent financial crisis which commenced in 2007, particularly in view of the growing number of bankruptcy cases in the Belarusian commercial courts. The purpose of this paper is to examine the varying legal treatments of employee entitlements in the case of employer insolvency (bankruptcy) and to encourage developing countries to use insurance to ensure the payment of employee entitlements which will ensure both the market strength and efficiency of the insolvency process
Nauki o Finansach = Financial Sciences, 2016, Nr 2 (27), s. 38-48
Keywords: ubezpieczenia; insolvency; bankruptcy; insurance; employee entitlements; upadłość (bankructwo); interesy ekonomiczne pracowników